Analisis Interaksi antara Tindakan Bullying dan Perkembangan Asertivitas pada Siswa Sekolah Dasar - Rahman, Maulida Aulia; Nurwahidah, Lina Siti; Muslihah, Neni Nadiroti; Destiani, Risma Fitri; Alani, Nabella (Universitas Sebelas Maret, 2025)
The prevalence of bullying behavior in elementary schools poses a significant threat to the development of students’ assertiveness, a vital component in fostering self-confidence and social resilience. This study seeks to examine the correlation between bullying incidents and the assertiveness development of students through a comprehensive literature review and an empirical case study involving sixth-grade students at SDN 1 Regol. Utilizing qualitative and quantitative methods including classroom observations, structured interviews, and questionnaires the findings reveal that the majority of students exhibit moderate levels of both bullying involvement and assertiveness. Notably, students subjected to higher levels of bullying tend to demonstrate lower assertiveness, while those with higher assertive capacities are more capable of articulating opinions and resisting unfair treatment. These results underscore the importance of assertiveness as a protective factor against bullying and advocate for its systematic cultivation through educational and character-building interventions from an early age. These findings affirm that enhancing students’ assertiveness can serve as an effective preventive strategy to reduce bullying in elementary school settings.Perilaku bullying yang marak terjadi di sekolah dasar berpotensi menurunkan kemampuan asertif siswa, yang sebenarnya sangat dibutuhkan dalam mengembangkan kepercayaan diri dan ketahanan sosial. Kajian ini bertujuan untuk menganalisis hubungan antara tindakan bullying dan perkembangan asertivitas siswa melalui tinjauan literatur serta studi kasus di kelas VI SDN 1 Regol. Penelitian yang dilakukan melakukan pendekatan kualitatif dengan metode deskriptif. Berdasarkan hasil observasi, wawancara, dan angket, ditemukan bahwa mayoritas siswa berada pada tingkat sedang dalam hal perundungan dan asertivitas, dengan kecenderungan bahwa siswa yang mengalami perundungan tinggi memiliki tingkat asertivitas rendah. Sebaliknya, siswa dengan kemampuan asertif tinggi lebih mampu mengekspresikan pendapat dan menolak perlakuan tidak adil. Kajian menunjukkan bahwa asertivitas berperan penting dalam membentuk ketahanan siswa terhadap perundungan, sehingga perlu dikembangkan melalui pendekatan edukatif dan karakter sejak dini. Hasil ini menegaskan bahwa peningkatan kemampuan asertif siswa dapat menjadi strategi preventif yang efektif dalam menurunkan tingkat perundungan di sekolah dasar.